Investigating 5G Wireless Networks Deployment with Diverse Frequency Bands for Basra City - Aymen M. Al-Kadhimi (Diyala Journal of Engineering Sciences)
The emergence of Fifth Generation (5G) technology has marked a significant advancement in communication networks offering unique speed, capacity, and reliability. However, the successful deployment of 5G networks in urban environments requires careful consideration of various factors, including frequency band selection and infrastructure planning. Since Iraq has not yet witnessed the 5G network implementation, studying how the frequency bands vary and affect performance will provide insights into a smoother migration toward the next-generation cellular systems. This research aims to investigate the feasibility and potential benefits of deploying 5G wireless networks in Basra City utilizing a diverse range of frequency bands at 1.8, 2.1, and 3.6 GHz. A cellular network was designed and analysed to identify the most suitable frequency bands for 5G deployment in this Iraqi city as a case study which can be then generalized for other terrain-like regions. The site locations, antenna heights, transmission power, and antenna down-tilt degree were optimized through three design scenarios. Furthermore, four measurement themes were adopted to evaluate network performance as coverages, power levels, Carrier-to-Interference (C/I), and power density measurement themes. The results showed that despite the network with 3.6 GHz band slightly recorded lower levels of power density, the 1.8 GHz band proved its outperformance compared with the other two bands in terms of coverage, capacity, and C/I. Besides, the 1.8 GHz based design served almost 100 km2 target area with excellent coverage. Consequently, the lower frequency 5G bands seemed to better accommodate users’ demands in Basra City with the outlined constraints.